Model-independent constraints on the cosmological anisotropic stress - Amendola, Luca; Fogli, Simone; Guarnizo, Alejandro; Vollmer, Adrian (Arxiv, 2013)
The effective anisotropic stress or gravitational slip $\eta=-\Phi/\Psi$ is a key variable in the characterisation of the physical origin of the dark energy, as it allows to test for a non-minimal coupling of the dark sector to gravity in the Jordan frame. It is however important to use a fully model-independent approach when measuring $\eta$ to avoid introducing a theoretical bias into the results. In this paper we forecast the precision with which future large surveys can determine $\eta$ in a way that only relies on directly observable quantities. In particular, we do not assume anything concerning the initial spectrum of perturbations, nor on its evolution outside the observed redshift range, nor on the galaxy bias. We first leave $\eta$ free to vary in space and time and then we model it as suggested in Horndeski models of dark energy. Among our results, we find that a future large scale lensing and clustering survey can constrain $\eta$ to within 10% if $k$-independent, and to within 60% or better at $k=0.1 h/$Mpc if it is restricted to follow the Horndeski model.